Transforming architecture through the realm of mixed-use typologies, with a bias to sports culture and lifestyle - Van Biljon, Ruben (School of Architecture, Planning and Geomatics, 2024)
This dissertation explores the relationship between architecture and sport through mixeduse spaces. Sport is an essential part of human development and livelihood, both as a participant and spectator. Unlike scripted entertainment, sport provides real-life entertainment that allows for human engagement. This project is a reference point for similar developments across various spaces as a starting point for future growth. It is located at the Bellville Velodrome site in the Northern suburbs of Cape Town. This project explores the challenging concept of incorporating sport into architecture while catering to the 'typical' everyday life architecture. The research conducted for this project focused on the various aspects that come together to create a mixed-use space with a sports bias. Including sport as a constant and intended element adds a new dimension to the traditional mixed-use typology. Understanding the crucial role of sport in human livelihoods is paramount to comprehending the principles followed throughout the dissertation. The design outcomes illustrate the findings and insights obtained through the research, resulting in a transformative structure that takes shape and connects to the surrounding development through the program and social intent. The focus building within the more extensive development becomes a seed within the greater development, as it allows the site to be reactivated and become relevant again, giving insight into becoming much more sustainable in the long term. There is a significant emphasis on sport due to its potential positive impact across generations.